2006
DOI: 10.1177/0193945906287215
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Minority Research Participation Through Community Organization Outreach

Abstract: Recruitment is one of the most significant challenges in conducting research with ethnic minority populations. Establishing relationships with organizations that serve ethnic minority communities can facilitate recruitment. To create a successful recruitment process, a strategic plan of action is necessary prior to implementing community outreach efforts. For this study population of women who were HIV+ and recovering from substance abuse disorder, the authors found that establishing trust with community organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 17 publications
2
101
0
Order By: Relevance
“…Although the willingness of Hispanics to participate in biomedical research is similar to that of Caucasians (Katz et al, 2006), a number of barriers affect their ability to participate. These may include familism, the cultural value of fulfilling family obligations and expectations (German, Gonzales, & Dumka, 2009;Polipnick, Hondras, Delevan, & Lawrence, 2005), access to care, lack of transportation, lack of child care, lost time at work, other family responsibilities, and mobile families (Alvarez, Vasquez, Mayorga, Feaster, & Mitrani, 2006). Immigrants may be reluctant to participate because of their documentation status, recent migration, lack of social infrastructure, language barriers, and low socio-economic status (Shedlin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the willingness of Hispanics to participate in biomedical research is similar to that of Caucasians (Katz et al, 2006), a number of barriers affect their ability to participate. These may include familism, the cultural value of fulfilling family obligations and expectations (German, Gonzales, & Dumka, 2009;Polipnick, Hondras, Delevan, & Lawrence, 2005), access to care, lack of transportation, lack of child care, lost time at work, other family responsibilities, and mobile families (Alvarez, Vasquez, Mayorga, Feaster, & Mitrani, 2006). Immigrants may be reluctant to participate because of their documentation status, recent migration, lack of social infrastructure, language barriers, and low socio-economic status (Shedlin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships are critical in Hispanic cultures. Engaging respected community leaders and organizations in research planning and execution can increase access (Alvarez et al, 2006;Reidy et al, 2012) and enhance the credibility of the study and those involved in the research process (Mendez-Luck et al, 2011). For example, trusted health care providers could help recruit participants (Unson et al, 2004) and abuelas (respected grandmothers) could be involved in delivering the interventions (Chapman & Perez-Escamilla, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Participant recruitment strategies utilized for this study have been reported elsewhere and focused on the Alvarez Recruitment Process Model, a mixed method approach (Alvarez, Vasquez, Mayorga, Feaster, & Mitrani, 2006;Breland-Noble et al, 2011). For the pilot phase of the study, the modes of participant entry were tracked using the Recruitment Process Log and the success of the research team in recruitment was evaluated using the Recruitment Success Factor.…”
Section: Recruitment Of the Pilot Samplementioning
confidence: 99%
“…A total of 106 parent-child dyads were randomized, 92 had exposure to the allocated interventions and completed baseline data collection, 79 were retained and provided data at the end of the intervention period, 3 months later, resulting in an 86% retention rate for those who attended the first session of the assigned interventions (refer to Figure 1). Both transportation to and from study sessions and on-site childcare services were provided free of charge to all study participants to overcome the most frequently cited barriers to study participation [20][21][22][23].…”
Section: Study Samplementioning
confidence: 99%